FORMASI IDEOLOGI PADA CERPEN ‘‘DZIKIR SEBUTIR PELURU” KARYA AGUS NOOR: ANALISIS HEGEMONI GRAMSCIAN - Wahyu Wiji Astuti (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This article is intended to see ideological formation in Agus Noor’s “Dzikir Sebutir Peluru”. The analysis is done by using Gramci’s hegemony theory that sees literary work as a part of hegemonic ideological formation or counter hegemonic (resistance) toward dominant discourse. The mechanism is done by finding out the dominant ideology through existed ideological formations. As the result of analysis, it is found that ideologies in this short story are socialism, humanism, religiosity, militarism, and nationalism. However, the most dominant ideology is socialist-humanist. Even though it is not delineated through the character, but the situation in this short story shows that there is capitalistic hegemony toward the country, and people’s reaction is a form of resistance toward an oppressive capitalization on low class society. A socialist-humanist ideology can be seen through each character in this short story.